The Impact of Foreign Direct Investment, Capital Formation, Inflation, Money Supply and Trade Openness on Economic Growth of Asian Countries - Yang, Xiuyun; Shafiq, Muhammad Nouman (iRASD Journal of Economics, 2020)
Economic growth is currently an essential phenomenon for emerging countries worldwide and has gained the researchers' intentions. Thus, the current study aims to examine the role of foreign direct investment (FDI), capital formation, inflation, money supply, and trade openness on the economic growth of Asian countries. The data has been extracted from the twenty emerging Asian countries from 2007 to 2018 using the most popular database named World Development Indicators (WDI). The fixed-effects model, along with the robust standard error, has been used for checking the impact of predictors on the economic growth of Asian countries. The results revealed that the predictors such as FDI, capital formation, money supply, and trade openness have positive association with economic growth, while inflation has a negative association with the economic growth of Asian countries. These findings are suitable for the new arrivals who want to examine this area in the future and for the regular traders who want to develop policies related to economic growth.